2023
DOI: 10.1186/s12967-023-04656-9
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the dynamics of the breast milk microbiome: impact of lactation stage and gestational age

Parul Singh,
Noora Al Mohannadi,
Selvasankar Murugesan
et al.

Abstract: Background Breast milk (BM) provides complete nutrition for infants for the first six months of life and is essential for the development of the newborn’s immature immune and digestive systems. While BM was conventionally believed to be sterile, recent advanced high throughput technologies have unveiled the presence of diverse microbial communities in BM. These insights into the BM microbiota have mainly originated from uncomplicated pregnancies, possibly not reflecting the circumstances of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…1B). This is consistent with previous studies showing detecting skin-associated taxa in milk in addition to Bifidobacteria 32,33 .…”
Section: Table 2)supporting
confidence: 93%
“…1B). This is consistent with previous studies showing detecting skin-associated taxa in milk in addition to Bifidobacteria 32,33 .…”
Section: Table 2)supporting
confidence: 93%
“…54 As breastfeeding continues, the microbial diversity within the milk increases, and beneficial bacteria, such as Veillonella, Bif idobacterium, and Streptococcus, proliferate and colonize the neonatal gut. 32,38,55 This dynamic transition is linked to the infant's growth and development, underpinning the stability and evolution of the gut microbiota. 32,55,56 During the 3−4 month postpartum period, the microbial composition of breast milk undergoes dynamic changes, primarily shifting between Proteobacteria and Firmicutes.…”
Section: Major Microbes In Human Breastmentioning
confidence: 99%
“…Damaceno et al (2017) analyzed breast milk microbiota quantitatively and found that colostrum has a higher absolute number of bacteria (3.9 log 10 CFU/mL), with Staphylococcus epidermidis being the most abundant . As breastfeeding continues, the microbial diversity within the milk increases, and beneficial bacteria, such as Veillonella , Bifidobacterium , and Streptococcus , proliferate and colonize the neonatal gut. ,, This dynamic transition is linked to the infant’s growth and development, underpinning the stability and evolution of the gut microbiota. ,, …”
Section: The Microbial Community In Human Breast Milk and Its Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…While human milk was initially assumed to be a sterile fluid, it is now widely accepted as a source of beneficial bacteria for infants, with around 10 4 colony-forming units per mL [1]. The human milk microbiome exhibits a low richness of bacteria, with Staphylococcus and Streptococcus being the most abundant and prevalent genera [2][3][4][5][6]. The remaining portion is comprised of other typical skin and oral taxa, including Corynebacterium and Cutibacterium [7], as well as lactic acid-producing bacteria such as Bifidobacterium and Lactobacillaceae, which are considered to contribute to infant health via their production of immune-modulating metabolites [8].…”
Section: Introductionmentioning
confidence: 99%